PENGARUH METODE MENGHAFAL DAN PRESENTASI TERHADAP PENINGKATAN ASPEK KOGNITIF DALAM MATA PELAJARAN PAI SISWA KELAS XI SMA DARUL HIKMAH BANGKALAN - Harirotul Jannah; Karina; Mushohihul Hasan (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2024)
Cognitive processes in student development are a very important component. The relationship between the two is directly through learning systems and methods so that it has an impact on student success in school. The purpose of this study was to determine how much influence memorization and presentations made by students on improving the cognitive aspects of grade XI students of Darul Hikmah Bangkalan High School in the subject of Islamic Religious Education. The purpose of this study was to determine how much influence memorization and presentations made by students on improving the cognitive aspects of grade XI students of SMA Darul Hikmah Bangkalan in the subject of Islamic Religious Education. This type of research is quantitative research. It is shown from the output of the ANOVA table that R2 x 100% 42.9 x 100% 42.9% simultaneous influence of the independent variable (memorization method and presentation) on the dependent variable. Since a significant value of 0.000 is smaller than 0.05, regression models can be used to predict the simultaneous influence of the independent variable on the dependent variable. Based on the results of the study, it can be concluded that there is an influence of memorization and presentation methods on the cognitive aspects of grade XI students of SMA Darul Hikmah Langkap Burneh Bangkalan. The influence of memorization and presentation methods on the cognitive aspects of grade XI students of SMA Darul Hikmah Langkap Burneh Bangkalan is 42.9% because this school has a learning system with memorization methods and increased self-confidence and the majority of respondents are from new students who are not familiar with learning methods.